2017
DOI: 10.1136/emermed-2016-206081
|View full text |Cite
|
Sign up to set email alerts
|

Violence-related ambulance call-outs in the North West of England: a cross-sectional analysis of nature, extent and relationships to temporal, celebratory and sporting events

Abstract: Objective: To explore the potential of ambulance call-out data in understanding violence to inform prevention activity.Method: Cross-sectional (2013Cross-sectional ( -2015 study examining the nature, extent and characteristics of violence-related ambulance call-outs (n=15,687) across North West England, and relationships with temporal, celebratory and sporting events. Results:The majority of call-outs were for males, with a mean age of 33 years. Most call-outs were to deprived (64.4%) and urban (65.4%) areas, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
(7 reference statements)
0
5
0
1
Order By: Relevance
“…To our knowledge, this is the only published research in scientific journals that uses ambulance records to study child injuries. As established by previous research, ambulance data can identify at-risk groups and establish where and when targeted prevention can be applied (Backe and Andersson 2008;Thomas et al 2011;Quigg et al 2017).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…To our knowledge, this is the only published research in scientific journals that uses ambulance records to study child injuries. As established by previous research, ambulance data can identify at-risk groups and establish where and when targeted prevention can be applied (Backe and Andersson 2008;Thomas et al 2011;Quigg et al 2017).…”
Section: Discussionmentioning
confidence: 91%
“…Trauma and Injury Intelligence Group, England (Quigg et al 2012); All Wales Injury Surveillance System (Lyons et al 2016); National Electronic Injury Surveillance System, USA (Nelson et al 2011); Canadian Hospitals Injury Reporting and Prevention Program (Crain et al 2016). A few studies have shown some utility in the use of ambulance service data in injury surveillance; whilst not solely focused on children, they indicate that such data could also be used to develop understanding and monitoring of injury at local and regional levels (Backe and Andersson 2008;Thomas et al 2011;Quigg et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ambulance attendance data can provide useful information regarding the identification of trends in alcohol use and aggression or violence within at-risk groups,38–41 in addition to information that is not available through ED data (eg, geographical location where an incident occurred) 42 43. Trends in all ambulance attendances by demographics will be investigated.…”
Section: Methodsmentioning
confidence: 99%
“…For one, they provide a broader source of information on potential violence than emergency department records because some victims of less serious violence are either treated on scene or refuse transport to the hospital (Giacomantonio et al, 2014). For example, Quigg and colleagues (2017) found in their examination of 3 years of violence-related ambulance calls that about one third of the calls did not lead to transfer to an emergency room or other health provider. Thus, these incidents would not appear in hospital data.…”
Section: Prior Researchmentioning
confidence: 99%